What Can Government Do to Help SMEs’s Product Sales through Halal Certificate? - Abdul Muhaimin Elyusufi; Maratun Saadah; Nugraha Nugraha; Maya Sari; Triyono Adi Tristanto (Budapest International Research and Critics University, 2022)
Halal is an important concept that facilitates and simplifies the consumption of food and beverage products, particularly for Muslim consumers. For a Muslim consumer, halal foods and drinks mean that the product has met the Shariah law requirements, whereas for a non-Muslim consumer, it represents the symbol of hygiene, quality, and safety when produced strictly under the Holistic Halal Assurance Management System. As a result, today's consumers are extremely concerned and are constantly conscious of what they eat, drink, and use. Muslim and non-Muslim consumers' awareness describes their perception and cognitive reaction to products or foods on the market. According to the study, developing Halal is a communally obligatory (fardhu kifayah) for Small Medium Enterprises (SMEs) and a personally obligatory (fardhu ain) for Muslim consumers. The Indonesian government has already recognized the importance of SMEs by implementing various policies and action plans, as well as introducing Halal-related programs to assist SMEs.